Effect of thermal history on the thixotropy of waxy crude. (2nd January 2016) - Pu, Hong Yu; Ai, Mu Yang; Zhang, Peng; Cen, Kang
ABSTRACT: An evaluation method combined with an experiment and theoretical analysis was proposed to study the effect of thermal history on the thixotropy of waxy crude, and the damage extent and recovery extent are the two crucial parameters in the evaluation. The results indicate the longer thermostatic time is, the higher heat-treatment temperature is, the faster the cooling rate is, and the more repeated heating times would cause a bigger damage extent and a smaller recovery extent. Moreover, the variation of damage extent and recovery extent are closely related to the state of structure (i.e., the more stable structure would cause bigger damage extent and a smaller recovery extent).